Slovak Republic : Report on the Observance of Standards and Codes (ROSC)-Data Module. (IMF Staff Country Reports; Country Report, 2005)
This report on the Observance of Standards and Codes (ROSC)-data module-provides an assessment of the Slovak Republic's macroeconomic statistics against the Special Data Dissemination Standard (SDDS), complemented by an assessment of data quality based on the IMF's Data Quality Assessment Framework. The assessment reveals that statistical agencies in the Slovak Republic generally have a legal and institutional framework that supports statistical quality, although the formal legal mandate to disseminate statistics should be made explicit. Resources are generally adequate for existing statistical programs.